Unlived memories: theoretical debates on the connection with the unexperienced past in contexts of student mobilization (Clepsidra - Interdisciplinary Journal of Memory Studies, 2025)
This article reviews three categories that allow us to think about ways of connecting with the past when directexperience is not available: postmemory, borrowed memory, and affirmative memory. Based on their definitions,contexts, and critiques, their scope and limitations are examined in order to understand the ways in whichcertain communities, particularly in the context of student mobilizations, redefine and activate references tothe past, assuming and claiming themselves as heirs. From a conception of memory as a social, political, andperformative process, the article reflects on unconventional ways of remembering that do not necessarily fit intofamiliar or exclusively traumatic frameworks. In doing so, it proposes a preliminary framework for analyzing thearticulation between memory and collective action in contemporary experiences.